2022
DOI: 10.1038/s41467-022-28358-w
|View full text |Cite
|
Sign up to set email alerts
|

In vivo mitochondrial base editing via adeno-associated viral delivery to mouse post-mitotic tissue

Abstract: Mitochondria host key metabolic processes vital for cellular energy provision and are central to cell fate decisions. They are subjected to unique genetic control by both nuclear DNA and their own multi-copy genome - mitochondrial DNA (mtDNA). Mutations in mtDNA often lead to clinically heterogeneous, maternally inherited diseases that display different organ-specific presentation at any stage of life. For a long time, genetic manipulation of mammalian mtDNA has posed a major challenge, impeding our ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The TAL effector proteins are linked to the I-TevI nuclease in mitoTev-TALE, rather than the FokI nuclease, as in mitoTALEN. Recently, a radically different approach for mtDNA editing has been reported, namely double-stranded DNA deaminase (DddA)-derived cytosine base editors (DdCBEs) ( Mok et al, 2020 ; Lee et al, 2021 ; Silva-Pinheiro et al, 2022 ). The DdCBE is composed of mitoTALE proteins, the interbacterial toxin DddA and an uracil glycosylase inhibitor.…”
Section: Current Methods For Mitochondrial Genome Editingmentioning
confidence: 99%
“…The TAL effector proteins are linked to the I-TevI nuclease in mitoTev-TALE, rather than the FokI nuclease, as in mitoTALEN. Recently, a radically different approach for mtDNA editing has been reported, namely double-stranded DNA deaminase (DddA)-derived cytosine base editors (DdCBEs) ( Mok et al, 2020 ; Lee et al, 2021 ; Silva-Pinheiro et al, 2022 ). The DdCBE is composed of mitoTALE proteins, the interbacterial toxin DddA and an uracil glycosylase inhibitor.…”
Section: Current Methods For Mitochondrial Genome Editingmentioning
confidence: 99%
“…Minczuk and collaborators successfully applied an in vivo proof-of-concept editing approach based on AAV-delivered DdCBE. They demonstrated the possibility of editing a specific mtDNA nucleotide in the heart of neonatal and adult mice [162], thus providing, for the first time, its potential translation to human somatic gene correction therapies to treat primary mitochondrial disease phenotypes. However, the identification of low-frequency off-target editing in the nuclear genome of mouse embryos demonstrates the solid need to optimize DdCBE for specific base editing on mtDNA, especially before being used for treating mitochondrial diseases [163].…”
Section: Mtdna Editingmentioning
confidence: 99%
“…Mouse experiments by others also provide in vivo evidence of long-lasting mtDNA editing. 4 , 5 In summary, this exciting work is an important step towards extension of prime editing to mtDNA to allow all 12 possible base-to-base changes so that this technology can be used to develop more relevant disease models, increase our abilities to control cell functions and hopefully offer patients suffering with debilitating mitochondrial defects improved treatment options (Fig. 1 ).…”
mentioning
confidence: 99%
“…A recent study showed the feasibility of in vivo mtDNA base editing in mouse hearts. 5 Using a cardio-tropic adeno-associated virus (AAV) serotype (AAV9.45) to deliver a DddA-derived cytosine base editor (DdCBE) to target the mouse mitochondrial Nd3 gene, the authors showed targeted editing of 10–20% in the cardiac tissue of mice analyzed 24-weeks after tail-vein injection of 1 × 10 12 AAV genomes per monomer per 8-week old mouse. 5 The mtDNA editing efficiency increased to 20–30% upon application of the same doses to neonatal mice via temporal vein injection.…”
mentioning
confidence: 99%
See 1 more Smart Citation